2018
DOI: 10.1371/journal.pone.0208063
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analyses and cost analyses in castration-resistant prostate cancer: A systematic review

Abstract: BackgroundTreatment of metastatic prostate cancer is associated with high personal and economic burden. Recently, new treatment options for castration-resistant prostate cancer became available with promising survival advantages. However, cost-effectiveness of those new treatment options is sometimes ambiguous or given only under certain circumstances. The aim of this study was to systematically review studies on the cost-effectiveness of treatments and costs of castration-resistant prostate cancer (CRPC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 112 publications
(230 reference statements)
1
18
0
Order By: Relevance
“…Four to six cycles administered on an outpatient basis compares very favourably to standard therapeutic regimens in formal cost-effectiveness studies performed in metastatic castrate-resistant prostate cancer. [33][34][35][36] Several studies have demonstrated an improvement in quality of life as well as in outcome measures following RLT. Side effects occur less frequently than with standard third-line therapies and are mostly treated without the need for hospital admission.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Four to six cycles administered on an outpatient basis compares very favourably to standard therapeutic regimens in formal cost-effectiveness studies performed in metastatic castrate-resistant prostate cancer. [33][34][35][36] Several studies have demonstrated an improvement in quality of life as well as in outcome measures following RLT. Side effects occur less frequently than with standard third-line therapies and are mostly treated without the need for hospital admission.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Ultimately, the cumulative lifetime costs of a patient's systemic therapies can be substantial, potentially dwarfing the cost of their original definitive local therapy. 20 The ideal of personalized medicine is to individualize care by identifying and targeting the unique molecular characteristics of a given patient or tumor; however, prostate cancer has historically been bereft of such targetable markers of response and resistance. 6,21 A validated and commercially available panel of biomarkers to guide the sequencing of subsequent treatments would be ideal, such that therapies that are likely to be ineffective could be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the onset of metastatic CRPC (mCRPC) appears to be an objective endpoint and has already been shown to be a good surrogate for overall survival in post-prostatectomy patients with second biochemical recurrence following salvage RT [ 18 ]. Moreover, these endpoints are also economically interesting as postponement of the onset of palliative ADT and/or mCRPC, might save a huge amount of money and improve the patient’s quality of life [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%